Challenges to Introducing Integrated Diabetes Care to an Inner-Regional Area in South Western Sydney, Australia - Reetu Zarora; Rati Jani; Freya MacMillan; Anna Pham; Ally Dench; David Simmons (International Journal of Integrated Care, 2020)
Introduction: Diabetes care often requires collaboration between general practitioners, allied health professionals, nurses, and/or medical specialists. This study aimed to describe the establishment of an integrated diabetes prevention and care approach in an area with limited access to primary and secondary care, and the challenges faced in its initial development. Description: A qualitative research approach to identify challenges was taken. Data included meeting minutes, observational data and reports involving local clinical and non-clinical stakeholders from June 2016- December 2018 and were thematically analysed. Discussion: Key challenges were low patient attendance in general practice, healthcare professional time, low participation at health promotion activities/peer support groups and diabetes education reflecting a low priority among people with and at risk of diabetes. Coordination between services remained a challenge. Conclusion: This study highlights the need to integrate new diabetes services with existing health activities in the community and the importance of allowing flexibility and regular contact with local healthcare professional and community to encourage their involvement. Regular meetings with the funders, internal and external stakeholders are key for sustainability and to adapt programmes to the local situation. Further work is needed to identify and implement strategies to overcome these challenges.